Synthesis and characterisation of water-soluble host and complexation studies with organic guests. - Khairuddean, Melati (Universiti Sains Malaysia, 2014)
A new cyclotetramer host with Schiff base linkages was synthesized and characterized. The reaction conditions were timized using gamma acid and formaldehyde in the presence of chromotropic acid as a catalyst.